Image-making – image management: White House photos and the political iconography of the Obama presidency. (1st June 2017) - Bernhardt, Petra
This article explores the role of Official White House Photos for political image-making and image management during the Obama presidency. Official White House photographers have privileged access to the president in domestic and public situations. They provide high-quality handout photos reflecting the intentions of the Obama administration and are responsible for some of the best-known photos of the President with strategic and historical value. Distributed via the social networking services of the White House, these photos can bypass mainstream journalistic outlets and limit what the public gets to see of certain situations or events. Taking the 'Years in Photos' galleries on the official White House Flickr account as a case study, the article qualitatively examines visual choices by the Obama presidency. The dataset consists of 639 photos posted between 2009 and 2015. The author draws on the method of political iconography to reconstruct core motifs of political self-representation. The analysis gives insight into visual strategies central to the President's image management by focusing on visual portrayals in different roles, settings and relation to others.